A WEB-BASED CORE CURRICULUM TO MEET CERTIFICATION AND TRAINING NEEDS FOR MEDICAL RESIDENTS - York, Joseph W.; Stapleton, Gerald; Sandlow, Leslie J. (Online Learning, 2003)
To meet institutional requirements for resident education in a core curriculum, the UIC College of Medicine implemented an online educational program called the UIC Online Core Curriculum. The UIC residency is composed of 1,000 physicians in training in 60 programs at 18 training sites. Its size and distribution create substantial obstacles to classroom-based delivery. An online format offered a viable alternative to meet the college’s need to present uniform content, document participation, and confirm resident achievement while addressing the residents’ need for flexibility with the Internet’s anytime, anywhere availability. Development of an online core curriculum included a focus group of program directors, residents, medical directors, and other faculty who were asked to suggest course topics that met not only the "letter" of the requirement, but also the spirit of the general competencies. These discussions resulted in a list of 13 topics, or modules. In July 1999, a pilot study involving first year UIC residents demonstrated the feasibility of the program. The following year, all UIC residents began participating. In the past two years residents from other institutions have been added to the program, resulting in a current participant base of approximately 3,800 residents nationwide. An analysis of 2,544 anonymous end-of-module surveys demonstrates that most residents can effectively participate with minimal technical problems. Consistent with the "anytime-anywhere" approach to web-based instruction, residents complete the modules not only at home but also while at clinical and other university sites. Overall satisfaction as reported by residents is high, and the majority agrees that the material presented is useful. Based on findings to date, the online core curriculum is an efficient and cost-effective method of providing a required program to a large, distributed population of learners while maintaining a high level of participant satisfaction.